A Prospective Study to Investigate Controlling Blood Pressure Under Transcranial Doppler After Endovascular Treatment in Patients With Occlusion of Anterior Circulation - Tao, Chunrong; Xu, Pengfei; Yao, Yang; Zhu, Yajuan; Li, Rui; Li, Jie; Luo, Wenwu; Hu, Wei (Frontiers in Neurology, 2021)
Objective: To evaluate the effect of blood pressure (BP) management with transcranial Doppler (TCD) guidance in patients with large-vessel occlusion in the anterior circulation after endovascular thrombectomy (EVT) on the long-term prognosis. Methods: This was a prospective study, 232 patients were non-randomized assigned to TCD-guided BP management (TBM) group or non-TCD-guided BP management (NBM) group. In the TBM group, BP was controlled according to TCD showing cerebral blood flow fluctuation. In the NBM group, BP was controlled according to the guidelines. The primary endpoint was a modified Rankin scale (mRS) score of 2 or lower at 90 days. The safety outcomes were the rates of symptomatic or any intracerebral hemorrhage (ICH) and mortality at 90 days. Results: 163 patients were assigned to the TBM group and 69 were assigned to the NBM group. In the propensity score matched cohort (65 matches in both groups), there was significant difference in the proportion of participants with mRS 0-2 at 90 days according to BP management (adjusted odds ratio 2.96, 95% CI 1.25 to 7.03). There was no difference in the rates of symptomatic or any ICH and mortality between two groups. In inverse probability weighted regression adjustment analysis, mortality decreased significantly in the TBM group than in the NBM group (adjusted odds ratio 0.86, 95% CI 0.76 to 0.99, p=0.03). Conclusion: In patients with acute ischemic stroke from large-vessel occlusion in the anterior circulation, BP management under TCD was superior to NBM in improving the clinical outcomes at 90 days. Trial registration: Chinese clinical trial registry, ChiCTR2000034443.